Dynamic bidirectional coupling of membrane morphology and rod organization in flexible vesicles - Stijn van der Ham; André F. V. Matias; Marjolein Dijkstra; Hanumantha Rao Vutukuri (Proceedings of the National Academy of Sciences, 2026)
The ordering of rod-like particles in soft, deformable containers emerges from the interplay of anisotropic interactions, geometric confinement, and boundary compliance. This competition couples internal particle organization to container morphology, producing behavior distinct from both rigid confinement and bulk systems. Such coupling is also relevant to biological contexts in which filamentous structures are confined by deformable membranes. Using a minimal model combining experiments and simulations of colloidal rods encapsulated in lipid vesicles, we show that soft confinement drives a bidirectional coupling between internal order and vesicle shape. This interplay gives rise to a phase diagram in which elongated vesicles promote nematic alignment at lower packing fractions, whereas higher packing fractions induce smectic-like ordering that reshapes vesicles into plate-like morphologies with increased bending energy. Furthermore, by controlling vesicle volume and membrane area, we demonstrate that boundary conditions enable reversible tuning of both vesicle shape and internal rod organization. These results establish a framework for dynamically controlling colloidal self-assembly in soft containers and provide insight into the organization of anisotropic building blocks in deformable, cell-like, confinements.